2015
DOI: 10.1093/mnras/stv1814
|View full text |Cite
|
Sign up to set email alerts
|

On the relative importance of different microphysics on the D-type expansion of galactic H ii regions

Abstract: Radiation hydrodynamics (RHD) simulations are used to study many astrophysical phenomena, however they require the use of simplified radiation transport and thermal prescriptions to reduce computational cost. In this paper we present a systematic study of the importance of microphysical processes in RHD simulations using the example of D-type H ii region expansion. We compare the simplest hydrogen-only models with those that include: ionisation of H, He, C, N, O, S and Ne, different gas metallicity, non-LTE me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Various authors have concluded that UV photoionisation is typically the most important process in regulating star formation on a cloud scale. Haworth et al (2015) find that additional processes beyond hydrogen photoionisation have a correcting factor of 10% at best. Radiation pressure mainly becomes important at very high surface densities, which principally affects smaller scales than the ones stud-ied here -see Crocker et al (2018) for idealised conditions and Kim et al (2018) for simulations with self-consistent star formation feedback.…”
Section: Feedback and Properties Of Uv Sourcementioning
confidence: 90%
“…Various authors have concluded that UV photoionisation is typically the most important process in regulating star formation on a cloud scale. Haworth et al (2015) find that additional processes beyond hydrogen photoionisation have a correcting factor of 10% at best. Radiation pressure mainly becomes important at very high surface densities, which principally affects smaller scales than the ones stud-ied here -see Crocker et al (2018) for idealised conditions and Kim et al (2018) for simulations with self-consistent star formation feedback.…”
Section: Feedback and Properties Of Uv Sourcementioning
confidence: 90%
“…We directly model the photoevaporative outflow, driven by external irradiation, using a radiation hydrodynamics and photodissociation region chemistry code torus-3dpdr, for which key relevant papers are Haworth & Harries (2012); Harries (2015); Haworth et al (2015); Bisbas et al (2015). This code was used to run models of externally irradiated discs in benchmark scenarios where there are semi-analytic solutions in Haworth et al (2016) -validating the approach.…”
Section: Numerical Methods and Disc Constructionmentioning
confidence: 99%
“…Elemental abundances are listed in Table 1, using the same values as Haworth et al (2015). We include the first few ionized states of each element, with ionization fractions calculated using the photoionization equilibrium equation (2.5).…”
Section: Initial Conditionsmentioning
confidence: 99%